Paradigm of Employment Law Protection in Indonesia between Legal Certainty, Justice, and Utility - M Hafizh Maulana; Daffa Akmal Manurung; Abdilbar Alfahrizi; Syahrul Agil (ISNU Sumatera Utara, 2024)
Labor law is an important instrument in realizing fair industrial relations through a balance between the interests of workers and employers. The dynamics of changes in labor regulations in Indonesia, especially after the amendment of the Labor Law through the Job Creation Law, have various consequences for the effectiveness of legal protection for workers as well as legal certainty for the business world. This study aims to analyze the paradigm of legal protection in the Indonesian labor system, identify the problems of implementing legal norms in industrial relations, and examine the direction of strengthening labor policies in realizing harmonious and sustainable industrial relations. The research uses a normative juridical method with a regulatory approach, a conceptual approach, and an analytical approach. Data was obtained through literature studies of laws and regulations, court decisions, legal doctrines, and various relevant scientific literature, then analyzed qualitatively. The results of the study show that Indonesia's labor law already has an adequate normative basis to protect workers' rights, but its implementation still faces various obstacles in the form of inequality of bargaining position between workers and employers, weak labor supervision, low legal compliance, and non-optimal industrial relations dispute resolution mechanisms. Regulatory changes also show a shift in orientation between worker protection and the need for labor market flexibility, so that a balance of policies is needed that is able to ensure legal certainty, protection of workers' rights, and the sustainability of the business world. Thus, the effectiveness of labor law is not only determined by the quality of the substance of the regulation, but also by the institutional strengthening, law enforcement, and legal culture of all industrial relations actors.